Atacama, de la crisis temporal a la crisis permanente. La minería del cobre en la segunda mitad del siglo xix - Venegas Valdebenito, Hernán (Revista de Historia Social y de las Mentalidades, 2025)
The  province  of  Atacama  was  one  of  the  most  dynamic  settings  for  economic transformations during the nineteenth century. Bear ing this context in mind, this essay synthesizes the changes of the copper mining indust ry during the second half of the nineteenth century, focusing on the instability fac tors caused by short cycles of economic depression and the susceptibility of local producer s to variations in the international market. It also analyses the opinion of the mining “gremio”  on these negative cycles, as well as their views on the problems of the working market, the difficulties on transportation, the foreign competition and the tributary policy applie d by the Chilean state. The article emphasizes on the different intensities of these cy cles of recession and their impact on the local productive groups, taking a closer look to th e economic differentiation process that this mining region experienced.
Keywords: Mining; copper industry; economic history